HUMAN CAPITAL IN THE CONCEPT OF OPEN SCIENCE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. Any economic system's development is only possible with capital participation. Over several centuries, a stable concept has emerged that considers human capital as an essential source of investment for innovation, scientific and technological progress, and the stable development of the state.At the same time, the practical realization of this concept is associated with such categories as education, science, healthcare, competencies, skills, professional abilities of employees, intellectual output, etc.The purpose of the article: The aim is to comprehensively investigate the innovative potential of human capital from the perspective of a driving force for progress in the knowledge age.Methods: Modern science is based on openness and accessibility as tools of scientific search and research. Human capital is an essential element of this search, expressed in intellectual abilities, self-development, and theoretical and practical generalizations. The basis for more profound research and generalizations is the study of internal and external influences on the formation of human capital and the definition of its role in the scientific sense.Results: Analyzing human capital through the prism of its structural formation, it is worth noting that its meaning has changed in different periods. In the twentieth century, when the economy was formed in the context of industrial development, human capital was focused on technological excellence and ingenuity.In the 21st century, economic development is dominated by the intellectual and scientific component, which is the basis for the functioning of the national system.Therefore, human capital in this period is gaining new meaning as a knowledge economy. In forming the country's national economy, the intangible form of capital is becoming increasingly important, where human resource is the basis of socio-economic development.Conclusions. As a result of the theoretical analysis of existing approaches and new proposals, the innovative economic development model is developing dynamically. Human (intellectual) capital is prioritized in this model, stimulating informatization and introducing modern scientific and technological innovations.Human capital is a complex phenomenon that adapts to modern innovative and technological changes and acts as an organizational motivator for achieving a high level of industrialization and a civilized environment.
Keywords: human, human capital, open science, innovation process, potential, human potential.